PENGARUH PENERAPAN PEMBELAJARAN GURINDAM TERHADAP PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TK DHARMA WANITA DESA TELUK PINANG KECAMATAN GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR - Noviani Yunita Sari; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This experimental study was conducted to determine the existence of a significant influence before and after being treated using teacher learning on the moral behavior of children aged 5-6 years in the Dharma Wanita Kindergarten of Teluk Pinang Village, Gaung Anak Serka District, Indragiri Hilir Regency. This study uses experimental methods with the design of one group pre-test post-test design. The sample used in this study was 17 students. The data collection techniques used are observation. The data analysis technique used the t-test using the SPSS 17.0 program. The research hypothesis is that there is an effect of the application of the learning method to the moral behavior of children aged 5-6 years in the Dharma Wanita Kindergarten of Teluk Pinang Village, Gaung Anak Serka District, Indragiri Hilir Regency. Based on data analysis after the tcount statistical test of -16,024 the two-party test means absolute prices, so the value (-) is not used (Sugiono, 2010) so that tcount (16,024) because the Sig.2-tailed value = 0.00 <0.05 . Then the researcher can conclude that there is a significant influence of moral behavior after the application of the learning of the teacher. The results of this study indicate that the application of mathematics learning to children's moral behavior is 39.89% and 60.11% is influenced by other factors.Key Words: Moral behavior, Gurindam learning